2021
DOI: 10.1021/acsami.0c20254
|View full text |Cite
|
Sign up to set email alerts
|

Novel Engineered Bacterium/Black Phosphorus Quantum Dot Hybrid System for Hypoxic Tumor Targeting and Efficient Photodynamic Therapy

Abstract: Intratumoral hypoxia significantly constrains the susceptibility of solid tumors to oxygen-dependent photodynamic therapy (PDT), and effort to reverse such hypoxia has achieved limited success to date. Herein, we developed a novel engineered bacterial system capable of targeting hypoxic tumor tissues and efficiently mediating the photodynamic treatment of these tumors. For this system, we genetically engineered Escherichia coli to express catalase, after which we explored an electrostatic adsorption approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…Interestingly, anaerobic bacteria can actively target the hypoxic tumor areas [ 30 ], and efficiently deliver therapeutic agents to the deep hypoxic regions of solid tumors. The bacterial cells can be loaded with drugs through chemical bonding [ 31 ], charge attraction [ 32 ] antigen–antibody binding [ 33 ] and biotin-streptavidin interaction [ 34 ]. Cai et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, anaerobic bacteria can actively target the hypoxic tumor areas [ 30 ], and efficiently deliver therapeutic agents to the deep hypoxic regions of solid tumors. The bacterial cells can be loaded with drugs through chemical bonding [ 31 ], charge attraction [ 32 ] antigen–antibody binding [ 33 ] and biotin-streptavidin interaction [ 34 ]. Cai et al .…”
Section: Discussionmentioning
confidence: 99%
“…This may be because CPT alters the tumor microenvironment and MnCO produces elevated ROS. ROS can degrade cellular protein and DNA, thus killing tumor cells (27,(31)(32)(33). An MTT assay test indicated that the cell viability of the control and ZIF-8 groups was minimally affected, while ZC alone or ZM induced moderate tumor growth inhibition (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…This research provided a promising nanoplatform for enhanced cancer chemo-photodynamic therapy, and highlighted the important role hypoxia-addressing PDT may play in the enhancement of antitumor immune response. Recently, genetically modified Escherichia coli ( E. coli ) with overexpressed human catalase was combined with photosensitizers such as chlorin e6 [ 156 ] and black phosphorus quantum dots [ 157 ], and enhanced PDT by catalyzing H 2 O 2 into O 2 in the tumor site.…”
Section: Strategies For Modulating Tumor Hypoxia In Pdtmentioning
confidence: 99%